Genome Wide Association Studies in Multiple Spinach Breeding Populations Refine Downy Mildew Race 13 Resistance Genes - Bhattarai, Gehendra; Shi, Ainong; Feng, Chunda; Dhillon, Braham; Mou, Beiquan; Correll, James C. (Frontiers in Plant Science, 2020)
Downy mildew, caused by the oomycete Peronospora effusa, is the most economically important disease on spinach. Fourteen new races of P. effusa have been identified in the last three decades. The frequent emergence of new races of P. effusa continually overcome the genetic resistance to the pathogen. The objectives of this research were to more clearly map the downy mildew resistance locus RPF1 in spinach, to identify single nucleotide polymorphism (SNP) markers associated with the resistance, and to refine the candidate genes responsible for the resistance. Progeny from populations generated from crosses of cultivars resistant (due to RPF1) to race 13 of P. effusa (Swan, T-Bird, Squirrel, Tonga) with race 13 susceptible cultivars (Whale and Polka) were inoculated and the downy mildew disease response determined. Association analysis was performed in TASSEL, GAPIT, PLINK, and GENESIS programs using SNP markers identified from genotyping by sequencing (GBS). Association analysis mapped the race 13 resistance loci (RPF1) to positions 0.39, 0.69, 0.94-0.98, and 1.2 Mb of chromosome 3. The associated SNPs were within 1-7 kb of the disease resistance genes Spo12784, Spo12719, Spo12905, and Spo12821, and 11-18 Kb from Spo12903. This study extended our understanding of the genetic basis of downy mildew resistance in spinach and provided the most promising candidate genes Spo12784 and Spo12903 near the RPF1 locus, to pursue functional validation. The SNP markers may be used to select for the resistant lines to improve genetic resistance against the downy mildew pathogen and in developing durably resistant cultivars.